AKTIVITAS LARVISIDAL EKSTRAK ETHANOL RUMPUT KEBAR (Biophytum petersianum Klotzsch) TERHADAP Aedes aegypti: LARVICIDAL ACTIVITY OF THE RUMPUT KEBAR (Biophytum petersianum Klotzsch) ETHANOL EXTRACT AGAINTS Aedes aegypti - Priyo Sambodo; Joko Prastowo; Soedarmanto Indarjulianto (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2012)
The aim of this research is to find out the larvicidal effect of rumput Kebar ethanol extract againts A. aegypti larvae. Seven hundred and twenty larvae of third instars were divided into 3 series and consist of 4 concentrations, (0 ppm, 2000 ppm, 2500 ppm and 3000 ppm) with 3 replications. Each group using 20 larvae of third instars were placed in 200 ml of treatment solutions. The effect of the treatments were monitored by counting the number of dead larvae after 24 h, 48 h and 72 h of exposure. Data was analyzed by ANOVA and Probit analysis was used to find out Lethal Concentration50 and LC90. The results showed that the average mortality is highest on the concentration of 3000 ppm after 72 h of exposure were 27 (36,15%). LC50 and LC90 values of 4770.626 ppm and 8264.651 ppm after 24 h of exposure.